PEMANFAATAN KARDUS BEKAS SEBAGAI MEDIA PEMBELAJARAN PUZZLE PADA MATA PELAJARAN IPA DI SD NEGERI INPRES VATWAHAN MALUKU TENGGARA - Renngiwur, Janaba (INSTITUT AGAMA ISLAM NEGERI AMBON, 2023)
The use of media in the learning process can generate new motivational desires and interests, and stimulate learning activities, even bringing psychological influences on students, especially elementary age students. The purpose of this study is to utilize used materials in the form of cardboard as a medium for learning science. The method used is descriptive qualitative, the research was conducted at Inpres Vatwahan Elementary School, in the odd semester of the 2022/2023 academic year for 19 grade VI students, the data collection technique was through observation, interviews and documentation. The results showed that the innovative work of educators using used goods in the form of cardboard as a medium for learning puzzles in science subjects was able to encourage the learning process to be more meaningful, active and fun. Learning media is useful in clarifying teaching material, overcoming space and time, encouraging students to be more active and can improve learning outcomes. Students also feel happy and enthusiastic, and are able to work together and solve problems. This learning media fulfills eductive, economic, social functions and develops students' experience and interpersonal intelligence so that cognitive, affective, psychomotor abilities are achieved to improve students' life skills. Puzzle media made from used cardboard that is no longer used is one of the many media that can be obtained from the surrounding environment which is useful for learning.Keywords: Learning Media, Puzzle, Cardboard